Kajian Keberkesanan Sistem Bas Kampus Induk USM - Saddum, Muhammad Nizar (Universiti Sains Malaysia, 2006)
Since 1999, USM’s Main Campus has implemented the bus system in order to reduce the number of vehicles in campus and to overcome congestion as well as to avoid accident in campus. The main objectives of this study are to study the effectiveness of the bus system in USM’s Main Campus and to highlight the issues related to the bus service. This study will also propose solutions to improve the effectiveness of the bus system. This methodology for this study involves collection of information from student affairs and development division of USM and the operator of the bus service. Questionnaires are distributed among students to obtain their views on the effectiveness of this bus system. Experiences from other universities were also used as guidance. Results from this study will indicate the facilities provided and the effectiveness of the bus system to students. Many issues and problems are highlighted and hopefully, this research will be able to help USM find the best solution for the bus service in the USM’s Main Campus.